Pemberdayaan Program Berkelanjutan Bagi Anak Asuh untuk Menanamkan Nilai-nilai Karakter Cerdas - Fadhilla Yusri; Afrinaldi Afrinaldi; Linda Yarni (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2021)
Poverty and neglect are unresolved problems in this country. Based on the results of the study, one of the two cities that have pockets of poverty in West Sumatra is Payakumbuh. Meanwhile, Payakumbuh has the largest export commodity in the livestock sector in West Sumatra. To overcome this, children from underprivileged families, orphans, orphans and abandoned children can be placed in orphanages. At the orphanage, children are expected to have their physical needs met, to develop their personality and to be able to continue their education. However, the reality is that the application of rules and punishments in orphanages makes the children not have intelligent characters as expected. Therefore, the assistance that can be given to assist the application of intelligent character in foster children is by providing group guidance services.